The causes and numbers of hospital admissions and deaths during the Korean War - Kun Hwang; Hun Kim; Chan Yong Park (Journal of Trauma and Injury)
Purpose The aim of this study is to present the causes and numbers of hospital admissions and deaths at hospital of Korean soldiers including civilian worker during the Korean War. Methods The War History of Rear Troops of the Korean War (confidential) published in 1955 by the Republic of Korea Army Headquarters was reviewed. Results During the war, 397,519 patients were admitted to hospitals (wounded in action, 53.9%; wounded on duty, 5.2%; due to disease, 40.9%). Most of the admitted patients were service members (92.4%), while the remaining were non-soldiers (7.6%). Among the 397,519 patients admitted to hospitals, 11,537 patients (2.9%) died. Most of the patients who died were service members (87.9%), and the remaining were non-soldiers (12.1%). The yearly numbers of died on duty did not vary much. The yearly number of deaths from diseases was lower in 1950, but suddenly increased in the next year and continued thereafter. Injuries accounted for more than three-fifths of the causes of death (n=7,444, 60.1%). Respiratory diseases corresponded to almost a quarter (n=2,799, 22.6%; 1,611 pulmonary tuberculoses and 1,188 other respiratory diseases). The most common category of causes of death was wounds (gunshot or stab; n=3,199, 25.8%), followed by wounds from fragments (n=3,173, 25.6%), pulmonary tuberculosis (n=1,611, 13.0%), and other respiratory diseases (n=1,188, 9.6%). Among the common causes of death, percentages of wounds and wound by fragments decreased over time; however, the deaths from respiratory disease increased. Conclusions These findings reflect several aspects of the public health and social situation during the Korean War.